Ipsative Assessment : Motivation through Marking Progress - Hughes, Gwyneth; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Ipsative assessment is a powerful new approach that provokes a radical rethink of the purposes and methods of assessment. This book presents a case for partially replacing competitive assessment with ipsative assessment, and it explores the possibilities and the challenges with research evidence and case studies.
Keywords: Science; Science, general